Islamic perspective of human talent identification and organizational justice: evidence from government linked companies in Malaysia / Idris Osman … [et al.] - Osman, Idris; Omar, Roaimah; Mahphoth, Mohd Halim; Mohd Hashim, Maryam Jameelah (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Managing human talents from religion perspective meets various challenges. The gaps of understanding and applications of Islamic principles have caused the discrimination and favouritism among the different candidates’ background. Talent identification from Islamic principles is relevant to be practiced in the modem world. This study was aimed to identify the level of talent identifications from Islamic perspective among government-linked companies (GLCs) in Malaysia and its effect on organizational justice. Mean was witnessed at 4.087, which represented high level of talent identifications from Islamic perspective. From the correlation analysis, Islamic human talents identification and organizational justice were shown a significant relationship one to another. The correlation between independent and dependant variables was positive and highly significant at the 0.01 level (2-tailed). Thus, the relationship between Islamic human talents identification variables and organizational justice were strong. This study was revealed the Islamic principles were the main key for the Malaysia’s GLCs to increase the number of potential leaders. Positive acceptance of Islamic principles will avoid unbiased and unethical exercises where justice meets in every single of task. Islamic principles allow employees to conform the good way to reach the successful in their life to perform greater and always meet the expectation of employers.